Standards for the Learning Process of Economics Teachers in State High Schools in Banda Aceh City - Nabela, Maya; Zakaria, *Zakaria; Amiruddin, Amiruddin (Riwayat: Educational Journal of History and Humanities, 2022)
The research, titled "Standard of Economic Teacher Learning Process at senior high school in Banda Aceh" aims to know the standards of the learning process and know what obstacles economic teachers face in implementing the standard of learning process. This research was conducted using quantitative methods with a type of declining research using frequency distribution techniques. The population in this study was an economics teacher at senior high school in Banda Aceh city of 47 people. The number of samples in this study amounted to 12 teachers of economic subjects with purposive sampling techniques that are sampling techniques with certain considerations. The results showed: (1) Obtained from the distribution of questionnaires that the standard of learning process of economics teachers at sma negeri in Banda city as a whole that entered into the category is very good number of 10 teachers, and 2 teachers implement the standard of learning process into the category of good. (2) Obtained from the results of the interview that the obstacles faced by teachers in carrying out the standards of the learning process are: when implementing the standard of learning process curriculum 2013 is very many forms of learning that must be implemented by a teacher, many components that must be noticed by teachers simultaneously in carrying out the standard of learning process.